Applicability of industry 4.0 technologies in the adoption of global reporting initiative standards for achieving sustainability. (10th July 2021) - Narula, Sanjiv; Puppala, Harish; Kumar, Anil; Frederico, Guilherme F.; Dwivedy, Maheshwar; Prakash, Surya; Talwar, Vishal
Abstract: Global reporting initiative (GRI) is the global standard of sustainability. It epitomizes the global best practice of triple bottom line, i.e., economic, environmental, and social impacts. This research is an expert-based analysis of 132 industry leaders and policymakers from 36 industries to evaluate the significance of Industry 4.0 (I4.0) technologies on GRI adoption. In the first phase, the influence of I4.0 on GRI standards is analyzed using basic descriptive statistics and analysis of variance. In the second phase, the significance of the GRI standards in the context of I4.0 is evaluated using the Fuzzy Analytical Hierarchy Process (AHP). The findings indicate that 85% of environmental, 65% economic, and 50% societal GRI standards are influenced by I4.0. It is also found that the influence on economic performance, indirect economic impacts, energy, and emissions are significantly high. Findings ratify that the social aspect, which is often overlooked, needs more focus in manufacturing. Most of the contemporary research on evaluating the impact of I4.0 on sustainability is conceptual, lacks comprehensiveness, and rigor by thorough testing and validation. This study is one of the pioneering works offering a conceptual framework that aids in integrating I4.0 with GRI. Highlights: An empirical analysis of 132 industry leaders and policy-makers from 36 industries was conducted. The findings show that 85% environment, 65% economic, and 50% societal GRI standards are impacted by I4.0 technologies. Social aspects are given low priority and need more focus while adoption. Findings would help the industry leaders for adopting GRI for achieving sustainability.